Production of bioprotein by aspergillus niger using solid state fermentation - Siti Fatimah Mohd Hanipiah (2013)
Bioprotein is a protein extracted from cultivated microbial biomass and can be produced using a number of different microorganism. The objective of this paper was to determine the influence of 4 types of physical factor optimization which are effect of substrates, effect of incubation time, effect of inoculum size and effect of the incubation temperature in bioprotein production. Four different types of agricultural residues were collected, dried and ground. The inoculum was prepared using Aspergillus niger in suspension and culture in solid state fermentation (SSF). The medium was supplemented at the same concentration with 70% of moisture content for every 5 grams substrate. . The 70 percent moisture is equal to 12 ml of solution which divided into 2 ml inoculum suspension and 10 ml of growth media solution. The samples were incubated at 37°C for 7 days. The samples were extracted by using phosphate buffer and the determination of protein was done by Bradford assay method. Optimization of physical factors were done and the optimum conditions for protein enrichment were sugarcane bagasse as the medium within 5 days incubation time, at 35°C of temperature and used of 3 ml of inoculum size.